Historiografi Islam Pertengahan: Penulisan Sejarah Ibnu Khaldun dan Karyanya Al-‘Ibar - Avicenna Al Maududdy (Polyscopia, 2026)
This study aims to examine the biography, scholarly works, and historiographical methods developed by Ibn Khaldun as one of the most influential figures in the evolution of Islamic historiography. The primary focus of the study is to analyze Ibn Khaldun's contribution to the reformulation of historical methodology through a critical, rational, and evidence-based approach. This research employs a library research method utilizing historical and historiographical approaches. The data were collected from a variety of primary and secondary sources, particularly Ibn Khaldun's Al-'Ibar and Muqaddimah, as well as supporting literature on Islamic historiography and Ibn Khaldun's historical thought. Data were analyzed using a descriptive-analytical method by examining Ibn Khaldun's concepts, methods, and intellectual contributions to historical writing. The findings reveal that Ibn Khaldun introduced a new paradigm in Islamic historiography through the application of dirayah historiography, a method emphasizing source verification, rational criticism, empirical observation, and the analysis of social factors influencing historical events. Through his monumental works, Al-'Ibar and Muqaddimah, he challenged the prevailing tradition of historical writing that accepted reports uncritically without rigorous verification. The study further demonstrates that Ibn Khaldun's most significant contribution lies in the development of a scientific approach to history by integrating historical and sociological analyses through the concepts of al-'umran and 'asabiyyah, thereby establishing him as a pioneer of critical historiography and one of the earliest founders of social science within the Islamic intellectual tradition.